Combination of farnesyltransferase and Akt inhibitors is synergistic in breast cancer cells and causes significant breast tumor regression in ErbB2 transgenic mice. - Balasis, M; Forinash, K; Chen, Y; Fulp, W; Coppola, D; Hamilton, A; Cheng, J; Sebti, S (2011)
The Akt activation inhibitor triciribine and the farnesyltransferase inhibitor tipifarnib have modest to little activity in clinical trials when used as single agents. In this article, preclinical data show that the combination is more effective than single agents both in cultured cells and in vivo. Combination index data analysis shows that this combination is highly synergistic at inhibiting anchorage-dependent growth of breast cancer cells. This synergistic interaction is also observed with structurally unrelated inhibitors of Akt (MK-2206) and farnesyltransferase (FTI-2153). The triciribine/tipifarnib synergistic effects are seen with several cancer cell lines including those from breast, leukemia, multiple myeloma and lung tumors with different genetic alterations such as K-Ras, B-Raf, PI3K (phosphoinositide 3-kinase), p53 and pRb mutations, PTEN, pRB and Ink4a deletions, and ErbB receptor overexpression. Furthermore, the combination is synergistic at inhibiting anchorage-independent growth and at inducing apoptosis in breast cancer cells. The combination is also more effective at inhibiting the Akt/mTOR/S6 kinase pathway. In an ErbB2-driven breast tumor transgenic mouse model, the combination, but not single agent, treatment with triciribine and tipifarnib induces significant breast tumor regression. Our findings warrant further investigation of the combination of farnesyltransferase and Akt inhibitors.